Comparison of the Use of Fable Animated Films and Fable Audio Stories in Improving Synopsis Writing Skills (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The purpose of this study was to compare the effectiveness of animated fables and audio fables in improving the synopsis writing skills of ninth-grade students at SMPN 4 Bungbulang. In the Indonesian language curriculum, synopsis writing is an important literacy skill that requires students to summarize, organize, and convey the content of a story effectively. However, many students find it difficult to identify story elements, maintain a consistent plot, and use appropriate language. This study conducted a quasi-experiment with a pretest-posttest control group design. Two groups were tested: the experimental group, which used animated story films, and the control group, which used audio stories. Data were collected through writing tests and response questionnaires given to students. Normality tests, homogeneity tests, t-tests, improvement score calculations, and effect sizes were used to analyze the data. The results showed that there was variation in.